Building trust with children and parents in the social work context: A scoping review - Heino, Eveliina; Kalm-Akubardia, Maija; Koskinen, Tanja; Jaakola, Anne-Mari; Kangas-Kalinen, Annamari; Lamponen, Tuuli; Sarin, Iida (Oxford University Press, 2026)
In this scoping review, we attempt to identify the consequences of trust in the relationship between professionals and clients (children and parents), elaborating upon how social work contextualizes the trust-building process and how professionals can build trust with clients. We first performed a literature search in March and April 2024, resulting in a total of 2,600 hits. After applying the exclusion criteria, we selected thirty-six peer-reviewed research articles published between 2014 and 2024 for our analysis. According to our review, trust enables a partnership between clients and professionals, and at best can support client healing as well as a generalized sense of trust. However, social work is a challenging context for the trust-building process given the power imbalance between clients and professionals, the high turnover of professionals, the complex service needs of clients, and structural problems within the system. Professionals can build trust with clients through different acts of care, using a strength-based approach, providing time and continuity, and working with families’ wider networks.